Enhance Facial Biometric Template Security using Advance Encryption Standard with Least Significant Bit - D, Gbolagade Morufat; Hambali, Moshood Abiola; Abdulganiyu, Oluwadamilare H.; Lawrence, E (ICSE (Institute of Computer Sciences and Engineering), 2022)
Security of data has been a major issue for many years which has lead to several challenges; loss of data and also allure hackers to where data are been stored. Biometric system to some extend has helped in combating these security issues, the major issues with the biometric system is how to properly secure the template been generated from hackers and unauthorized users. In this paper we combine cryptography and steganography to enhance security of biometric templates using the advance encryption standard (AES) and the least significant bit (LSB) technique to encrypt these templates and secure it from hackers, Cryptography and Steganography are the two widely employed techniques for securing and hiding data. The center of attention of this paper is the potency of combining cryptography and stenography techniques to improve the security of biometric templates.